The influence of technology readiness on actual use of electronic evaluation forms among internship examiners in higher learning institutions - Zalinawati Abdullah,; Mohd Khairi Ismail,; Nurul Ulfa Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
When integrated with digital workflows, each form input may activate the next process step, increasing the pace of operations. Compiling and utilizing information from a completed form can generate additional outputs. This study examines the influence of technology readiness dimensions namely optimism, innovativeness, discomfort, and insecurity on the actual use of electronic evaluation forms among examiners of internship students in business schools of higher learning institutions. Furthermore, the study also examines the influence of actual use on commercialization. As a result, this study may provide significant insights into the human aspects influencing technology usage behaviour in educational settings and offer practical suggestions for bridging the gap between technology readiness, actual usage, and commercial value in business schools. The data were collected through an online survey of 119 examiners and analysed using IBM SPSS Version 24 and SmartPLS 4.0.9.2. The findings indicate that optimism has a positive influence on the actual use of electronic evaluation forms, whereas innovativeness, discomfort, and insecurity do not. Additionally, the actual use of evaluation forms positively impacts commercialization. Thus, the findings provide significant contributions to theory and practice. The study highlights the importance of optimism in driving electronic evaluation and usage, prompting a rethinking of technology integration strategies. It encourages discussions and recommendations for academics and practitioners to optimise the use of electronic evaluation forms in business schools, maximising their potential for commercialization within educational landscapes.